2008
DOI: 10.1111/j.1365-2966.2008.13113.x
|View full text |Cite
|
Sign up to set email alerts
|

The SCUBA HAlf Degree Extragalactic Survey (SHADES) – VII. Optical/IR photometry and stellar masses of submillimetre galaxies

Abstract: We present estimates of the photometric redshifts, stellar masses and star formation histories of sources in the Submillimetre Common-User Bolometer Array (SCUBA) HAlf Degree Extragalactic Survey (SHADES). This paper describes the 60 SCUBA sources detected in the Lockman Hole covering an area of ∼320 arcmin 2 . Using photometry spanning the B band to 8 μm, we find that the average SCUBA source forms a significant fraction of its stars in an early period of star formation and that most of the remainder forms in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
109
2
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 64 publications
18
109
2
1
Order By: Relevance
“…In order to build up the stellar mass of one SMG, five such galaxies would need to form stars continuously at a rate of 20 M yr −1 , a value more likely to be sustainable over several Gyr. The latter scenario is consistent with the results of Dye et al (2008) based on observed optical to mid-IR data of 51 SMGs with photometric redshifts. They found that approximately half the stellar mass in SMGs has been formed over a long (∼1-2 Gyr) period of approximately constant star formation activity.…”
Section: Star Formation Ratessupporting
confidence: 81%
See 1 more Smart Citation
“…In order to build up the stellar mass of one SMG, five such galaxies would need to form stars continuously at a rate of 20 M yr −1 , a value more likely to be sustainable over several Gyr. The latter scenario is consistent with the results of Dye et al (2008) based on observed optical to mid-IR data of 51 SMGs with photometric redshifts. They found that approximately half the stellar mass in SMGs has been formed over a long (∼1-2 Gyr) period of approximately constant star formation activity.…”
Section: Star Formation Ratessupporting
confidence: 81%
“…Due to the coarse resolution of SCUBA, localizations derived from high-resolution radio maps had to be used to measure their spectroscopic redshifts . Lots of studies have addressed the issue of characterizing the nature of SMGs (Egami et al 2004;Greve et al 2004Greve et al , 2005Smail et al 2004;Swinbank et al 2004Swinbank et al , 2006Swinbank et al , 2008Takagi et al 2004;Alexander et al 2005;Borys et al 2005;Kovács et al 2006;Laurent et al 2006;Pope et al 2006;Tacconi et al 2006Tacconi et al , 2008Takata et al 2006;Younger et al 2007Younger et al , 2008Younger et al , 2009aClements et al 2008;Coppin et al 2008;Dye et al 2008Dye et al , 2009Hainline et al 2009;Perera et al 2008;Scott et al 2008;Austermann et al 2009;Devlin et al 2009;Eales et al 2009;Murphy et al 2009;Murphy 2009;Tamura et al 2009;Weiß et al 2009b;Aravena et al 2010, some of these works were based on surveys with sensitivity worse than 3 mJy quoted above). However they were usually based on limited samples ( 20 sources), limited wavelength coverage or photometric redshifts.…”
Section: Introductionmentioning
confidence: 99%
“…This has primarily been done with Spitzer MIPS 24µm maps, as they cover large areas of sky to sufficient depths (e.g. Pope et al, 2006;Dye et al, 2008). While mid-infrared emission does roughly correlate with far-infrared emission, a few aspects of mid-infrared emission complicate the relation.…”
Section: Radio Counterpartsmentioning
confidence: 99%
“…Because this study was aimed at investigating X-ray detected SMGs (to compare stellar masses to black hole masses), contamination of the stellar masses by AGN is a potential issue, particularly because rest-frame K-band luminosities were used in the derivation. Dye et al (2008) determine the stellar masses for galaxies in the SHADES survey with only 8 bands of photometry utilizing the synthetic spectra of Bruzual & Charlot (2003); while they find comparable stellar masses to the work of Borys et al (2005), the margin of uncertainty from lack of observational constraints dominate.…”
Section: Stellar Massesmentioning
confidence: 99%
“…They represent a major phase of star formation at early epochs and are also characterized by high stellar masses (e.g., Borys et al 2005). They are thus ideal candidates to be the precursors of local massive elliptical galaxies (e.g., Blain et al 2002;Dye et al 2008;Lonsdale et al 2009, hereafter Lo09, and references therein). Nearly all of the enormous UV energy produced by their massive young stars is absorbed by interstellar dust and re-emitted at far-infrared wavelengths, with their far-infrared luminosity (L FIR ) able to reach 10 13 L .…”
Section: Introductionmentioning
confidence: 99%